Total Quality Management Practices in Malaysia Healthcare Industry: A Survey Result - Md Fauzi Ahmad; Phoi Soo Nee; Nik Hisyamudin Muhd Nor; Chan Shiaw Wei; Mohd Fahrul Hassan; Nor Aziati Abdul Hamid (International Journal of Supply Chain Management, 2017)
Total quality management (TQM) is the management strategy that involves all organizational functions with the purpose on satisfying customers and achieving the vision and mission of the organizations. The aim of total quality management (TQM) is to achieve customer satisfaction. Healthcare industry is very important in Malaysia for providing good healthcare services to public. However, failure to improve quality and efficiency is a big challenge in a healthcare industry in order to increase quality healthcare services. The objectives of this research are to identify the extent level of TQM implementation; and to determine the impact of TQM implementation on business sustainable in healthcare industry. Quantitative approach has been chosen as the methodology of this study. The survey respondents targeted in this research are staffs in Malaysia private clinic. 70 respondents have participated in this research. Data were analysed by Statistical Package Social Science (SPSS). Analysis result showed that there was a positive significant relationship between TQM practices and business sustainable (r=0.774, P0.05). All TQM factors have significant relationship with business sustainable factors. The findings of this research will help healthcare industry to understand a better and deeper valuable information on the impact of TQM implementation towards business sustainable in Malaysia healthcare industry.